2020
DOI: 10.5511/plantbiotechnology.20.0516a
|View full text |Cite
|
Sign up to set email alerts
|

Hatching stimulation activity of steroidal glycoalkaloids toward the potato cyst nematode, <i>Globodera rostochiensis</i>

Abstract: Cyst nematodes (Globodera spp. and Heterodera spp.) are highly evolved sedentary endoparasites that are considered as harmful pests worldwide. The hatching of the dormant eggs of cyst nematodes occurs in response to hatching factors (HFs), which are compounds that are secreted from the roots of host plants. Solanoeclepin A (SEA), a triterpene compound, has been isolated as HF for potato cyst nematode (PCN) eggs, whereas other compounds, such as steroidal glycoalkaloids (SGAs), are also known to show weak hatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The hatching assay, using eggs of G. pallida , showed that SolA is extremely active in sub-nM concentrations, which is much lower than the values reported for glycoalkaloid hatching stimulants such as α-tomatine, which induces only average hatching rates at µM concentrations (Shimizu et al 2020 ). Furthermore, from our results, G. pallida seems to be equally sensitive to SolA compared to G. rostochiensis and G. tabacum , which were studied by Sakata et al ( 2020 ).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The hatching assay, using eggs of G. pallida , showed that SolA is extremely active in sub-nM concentrations, which is much lower than the values reported for glycoalkaloid hatching stimulants such as α-tomatine, which induces only average hatching rates at µM concentrations (Shimizu et al 2020 ). Furthermore, from our results, G. pallida seems to be equally sensitive to SolA compared to G. rostochiensis and G. tabacum , which were studied by Sakata et al ( 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…Hence, the root exudate probably contains additional, unknown, hatching stimulants, causing a high hatching rate despite the low SolA concentration. As already discussed, tomatidine and α-tomatine may contribute to induce hatching, but are not very effective and alone cannot explain the hatching rates obtained (Shimizu et al 2020 ). Other host species of PCN such as potato, are known to produce a range of hatching factors as well, like α-chaconine, α-solanine and solanidine (Stobiecki et al 2003 ; Shakya and Navarre 2008 ), which induce hatching in G. rostochiensis , but only at nM concentrations (Ochola et al 2020 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Authentic samples of α-solanine 9 , α-chaconine 10 , and solanidine 12 were purchased from Sigma-Aldrich, and α-tomatine 6 was purchased from Tokyo Chemical Industry Co., Ltd. ( 22S , 25S )-spirosol-5-en-3β-ol 3 were isolated in our laboratory from tomatidine 4 (Chromadex), respectively, using HPLC 35 , 36 . α-Solamarine 7 and β-solamarine 8 were purified from the diploid potato clone 97H32-6 and the chemical structures were confirmed using NMR in our laboratory 37 .…”
Section: Methodsmentioning
confidence: 99%
“…The variation in the glycinoeclepin structure suggests that more solanoeclepins might exist and that their hatch-inducing activity can vary. In addition to solA, some weaker HFs have been identified, such as α-chaconine, α-solanine, solasodine, and solanidine [12,13]. Apart from hatch-inducing compounds, hatch inhibitors (HIs) are also known.…”
Section: Introductionmentioning
confidence: 99%